UPAYA DIPLOMASI INDONESIA DALAM PERLINDUNGAN JAMAAH HAJI MELALUI INTEGRASI SISKOHAT (SISTEM INFORMASI DAN KOMPUTERISASI HAJI TERPADU) DAN NUSUK - Hernanda Rezly Cantona; Satriya Wibawa (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Indonesian diplomacy in strengthening the protection of Hajj pilgrims through the integration of SISKOHAT and Saudi Arabia’s Nusuk platform. As the world’s largest hajj-sending country, Indonesia bears a constitutional responsibility to protect more than 200,000 of its citizens who annually fall under Saudi Arabian jurisdiction. Conventional protection mechanisms that rely on physical documents, manual coordination, and disconnected data systems have proven inadequate to address the complexity of pilgrim protection on a contemporary hajj scale. This study uses a qualitative approach through document study, semi-structured interviews, and internet-based research. Using Okano Heijmans’ protection diplomacy framework and Bjola’s digital diplomacy concept, this study analyzes how the SISKOHAT-Nusuk integration, scheduled to be fully operational by the 2026 hajj season, transforms pilgrim protection mechanisms in the dimensions of legality, service access, medical response, and Indonesia’s diplomatic bargaining position. The results show that this integration results in a structural strengthening of protection, characterized by data-based identity verification, guaranteed access to the digitized Masyair area, and the integration of pilgrim medical records. However, this transformation has also created new vulnerabilities in the form of digital literacy gaps, risks of system disruptions, and data sovereignty issues. This research contributes to the literature on protection diplomacy in non-Western contexts and offers policy recommendations for optimizing pilgrim protection in the digital era.